Kebijakan Pemangkasan Struktur Birokrasi di Indonesia - M Najibur Rohman; Daud Rismana (Faculty of Sharia, Islamic State University (UIN) Prof. K.H. Saifuddin Zuhri Purwokerto, Indonesia, 2021)
This article aims to find out the policy formulation of reducing the bureaucratic structure in Indonesia and the impact that occurs as its result. This article is a literature research using literature review as a primary legal source supported by secondary data which is the result of implementing regulations in the field. The results of the study indicate that the formulation of the policy of reducing the bureaucratic structure in Indonesia is to eliminate echelon III to echelon V. The main purpose of this cut is to streamline government services through government employees (civil servants). As the impact, organizationally, this cut is not ideal because it is carried out in parallel with the preparation of SOTK. In terms of human resource management, this cut has an impact on the transfer of administrative officials to functional positions that are more competency-based or expertise-based.